Структура порового пространства биосовместимых порошковых сплавов на основе TiNi - Пахолкина, София Александровна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The selected mode o f obtaining a porous alloy based on TiNi by the SHS and diffusion sintering methods is characterized by different pore space conditions. The first method yielded large-porous samples with an average pore size o f 171 pm, porosity o f 64 %, and permeability in the longitudinal direction o f 590 D. The pore space of SHS samples is characterized by a complex structure o f interconnected pores due to the layer-by-layer synthesis mode, the product o f which is a porous-permeable material with a high proportion o f open pores. The sample obtained by diffusion sintering method retains the individuality o f the initial particles o f TiNi powder. A small amount o f liquid phase in the sintering process leads to preservation o f the original structure o f the powder in the composition o f inter-pore bridges. The average pore size o f the material obtained by sintering was 123 pm, the porosity 55 %. The permeability in the longitudinal direction was 20 D.